Joint Reading of Informational Science Text Versus Narrative Stories: How Does each Affect Language and Literacy Abilities Among Kindergarteners?. Issue 8 (17th November 2018) - Nevo, Einat; Vaknin-Nusbaum, Vered
Abstract : The effectiveness of a literacy intervention program based on a joint interactive reading of informational science texts in increasing children's science vocabulary, language and literacy skills, delivered by the kindergarten teacher, was examined in 34 Hebrew-speaking kindergarten children exhibiting different levels of emergent literacy skills. The impact of the informational science text intervention was compared to that of a similar program based on narrative stories. Post-intervention, both groups improved their domain-specific vocabulary – science or narrative – but the change in domain-specific vocabulary learning was lower in the informational science group as opposed to the narrative group. Improvement was also found with regard to general vocabulary, print concepts, and listening comprehension following both interventions. Change in scientific vocabulary was positively related with change in morphological awareness, change in print concepts, and listening comprehension. No such findings were found with regard to narrative vocabulary. The study suggests that a short informational science intervention program can enhance science vocabulary and literacy skills in kindergarten children and should be used more often in kindergartens.